ADOPTING INNOVATIVE METHOD AND COMPARATIVE EVALUATION OF SWETHA PARPATI MENTIONED IN AYURVEDIC LITERATURE (International Journal of Ayurveda and Pharma Research, 2017)
In Ayurveda, the study of the therapeutic uses and effects of drugs means Pharmaco-therapeutic is described under the branch of Rasashastra which mainly incorporates inorganic, herbo-mineral and metallic pharmaceutical preparations namely Khalviya Rasayana, Parpati Rasayana, Pottali Rasayana and Kupipakwa Rasayana. This article aims for the comparative assessment of Swethaparpati coming under Parpatikalpa mentioned as per reference of Sidhayogasangraha, AFI with another reference of Rasodharatantra. According to the first two references the ingredients used for the preparation are Suryakshara, Sphatika and Navasadara and as per the third reference ingredients like Tankana and Karpura are added. Here a detailed review of literature has been collected regarding the potential of the above mentioned individual ingredients along with the recent research updates regarding individual ingredients used in the production of Swetha Parpati according to both the references it also incorporate research updates on the formulation Swetha Parpati. This article also aims pharmaceutical standardization of standard method adopted in process of production of Swethaparpati with the alteration made from the usual method adopted in preparation of Parpati Kalpana that will help for developing new improved SOP regarding the formulation. This paper also aims in projecting the improved therapeutic value which could be generated by addition of new ingredients mentioned as per reference of Rasodharatantra.